Symposium 2: Nurses’ experiences from a flexible online course in a higher education learning initiative - Holmström, Malin Rising; Häggström, Marie (Proceedings of the International Conference on Networked Learning, 2024)
Remote healthcare is developing at a rapid pace to create high-quality, efficient, and financially sustainable care. The article aims to describe and explore nurses’ experiences of networked learning before and after participation in a higher education lifelong learning initiative. The study was conducted in primary healthcare and hospital units in Sweden with ten nurses (eight women and two men), where the participants answered a web-based questionnaire before and after participating in an online course, Digital Competence in Care. The data were analysed with descriptive statistics and qualitative content analysis. The results show increased development of nurses’ competence and learning. The mean of digital competence among all participants increased from 4.4 to 8.9 on a scale of 0-10 and the mean of expectations for learning among all participants increased from 7.1 to 9.2 on a scale of 0-10. Furthermore, two themes were identified: Lifelong learning important and urgent for nurses and Networked learning a flexible way to strengthen learning and think outside the box. The content and design of DCC were experienced as relevant for the participants, and networked learning was perceived as a way of developing and strengthening learning and competence. The participants indicated that sharing experiences and networking with others supported them in solving problems in their daily work, “thinking outside their own box,” and putting ideas into action together to support a critical and responsible attitude. The use of authentic work-related problems in the course assignments was experienced as a good thing, as it supported the nurses in their everyday work. Finally, the participants described how they became more courageous and confident in their ability to communicate and work securely digitally, and also that their new knowledge and competence were relevant to the continued development of digitalisation in healthcare settings and medical care, as colleges and leaders turned to them for support and advice.